Attitudes towards the timing of first birth and gender-based violence in rural Niger: Are adolescent wives with attitudes different from their husbands and peers at a higher risk of intimate partner violence and reproductive coercion? - Shweta Tomar; Holly Baker; Hachimou Amani; Kevin Iredell; Kadidiatou Boubacar Moussa; Abdoul-Moumouni Nouhou; Jennifer Gayles; Elizabeth Reed; Susan Kiene; Rebecka Lundgren; Jay Silverman (PLoS ONE, 2025)
Background Intimate partner violence (IPV) and reproductive coercion (RC) significantly impact women’s and girls’ health. Among other determinants, wives’ discordance from their husbands’ fertility-related attitudes may increase husbands’ use of IPV and RC. This study aims to assess if such discordance in attitudes towards the timing of the first pregnancy is associated with IPV and RC among adolescent wives (AWs) in rural Niger. Methods Data from 918 AWs, their husbands, and peers from a baseline assessment for a community-based family planning program in Niger were analyzed. Multilevel logistic regression models tested the association between AWs’ attitudinal discordance and their experience of IPV and RC. Results AWs with discordant attitudes who preferred a shorter wait for childbirth than what their husbands preferred had 0.35 times lower odds of experiencing physical IPV, while those who preferred a longer wait had higher odds of experiencing sexual IPV (AOR = 2.56) and RC (AOR = 2.56). Similarly, relative to the collective attitudes of husbands in the village, the AWs with discordant attitudes supporting no delay in first childbirth had 0.23 times lower odds of experiencing physical IPV, while those who supported delayed childbirth had 6.11 times greater odds of experiencing sexual IPV. Conclusion Violence prevention interventions need to address social norms that tie women’s values to reproductive choices. Empowering women, engaging men, and involving the community in supporting women’s autonomy in fertility decisions are crucial. Additionally, integrating IPV and RC mitigation into family planning programs is essential, especially in places like Niger, where fertility decisions are tied to cultural norms.